The impact of face masks on performance and physiological outcomes during exercise: a systematic review and meta-analysis - Shaw, K. A.; Zello, G. A.; Butcher, S. J.; Ko, J. B.; Bertrand, L.; Chilibeck, P. D. (Applied Physiology, Nutrition, and Metabolism, 2021)
Face masks are promoted for preventing spread of viruses; however, wearing a mask during exercise might increase CO2 rebreathing, decrease arterial oxygenation, and decrease exercise performance. A systematic review and meta-analysis was conducted on the impact of wearing a mask during exercise. Data sources included SPORTDiscus, PubMed, and Medline. Eligibility criteria included all study designs comparing surgical, N95, or cloth masks to a no mask condition during any type of exercise where exercise performance and/or physiological parameters were evaluated. Healthy and clinical participants were included. Mean differences (MD) or standardized mean differences (SMD) with 95% confidence intervals were calculated and pooled effects assessed. Twenty-two studies involving 1573 participants (620 females, 953 males) were included. Surgical, or N95 masks did not impact exercise performance (SMD -0.05 [-0.16, 0.07] and -0.16 [-0.54, 0.22], respectively) but increased ratings of perceived exertion (SMD 0.33 [0.09, 0.58] and 0.61 [0.23, 0.99]) and dyspnea (SMD 0.6 [0.3, 0.9] for all masks). End-tidal CO2 (MD 3.3 [1.0, 5.6] and 3.7 [3.0, 4.4] mm Hg), and heart rate (MD 2 [0,4] beats/min with N95 masks) slightly increased. Face masks can be worn during exercise with no influences on performance and minimal impacts on physiological variables. PROSPERO registration: CRD42020224988. Novelty: • Face masks can be worn during exercise with no impacts on performance and minimal impacts on physiological variables.